Phosphate Ion Release and Alkalizing Potential of Three Bioactive Dental Materials in Comparison with Composite Resin - Shahin Kasraei; Sahebeh Haghi; Sara Valizadeh; Narges Panahandeh; Sogol Nejadkarimi (International Journal of Dentistry)
Aim. Several new bioactive compounds were recently introduced to the market with favorable ion release, tooth remineralization, and alkalizing potential. This study sought to compare the phosphate ion release and alkalizing potential of three bioactive materials in comparison with composite resin. Methods. Thirty-six discs (2 × 6 mm) were fabricated from Fuji II LC resin modified glass ionomer (RMGI), Activa BioActive, Cention N, and Z250 composite in plastic molds. The specimens were stored in distilled water for 24 and 48 h and 6 months. Half of the specimens were used to assess the phosphate ion release while the other half were used to assess the alkalizing potential 1 h after pH drop from 6.8 to 4. Phosphate ion release was quantified by a spectrophotometer while the pH value was measured by a pH meter. Data were analyzed using two-way ANOVA, one-way ANOVA, and Tukey’s HSD test (for pairwise comparisons) at 0.05 level of significance. Results. At 24 h, the maximum phosphate ion release in distilled water occurred in the Fuji II LC group followed by Cention N, Activa BioActive, and Z250. At 6 months, Cention N followed by Activa BioActive showed higher phosphate ion release than Fuji II LC and Z250. No significant difference was noted between Activa BioActive and Cention N at any time point. All materials, except for Z250, increased the pH of the environment. Fuji II LC had maximum alkalizing effect at all time points followed by Cention N and Activa BioActive. Conclusion. Use of bioactive compounds is a promising method to ensure phosphate ion release, and can have a positive effect on tooth remineralization over time. Also, bioactive compounds can alkalize an acidic environment.